Trends of incidence of colorectal cancer in Iran, 2003–2010 - Seyedeh Leila Dehghani (Revista Latinoamericana de Hipertensión, 2019)
Introductionand and Background: As the third leading reason of death, cancers have a special place in the Iranian health system. This study to investigate the incidence trends of colorectal cancer in Iran from 2003 to 2010. Methods: The recorded data for colorectal cancer cases in National Cancer Registry System were obtained from the Center for Disease Control & Management of Ministry of Health. The codes from 18 to 21 among cancers were selected for colon and rectum cancers. The significance of incidence rate trends was tested through Poisson regression. Results: In this study, 38,712 cases of colorectal cancer were observed for 8 years in Iran, which increased from 2882 cases in 2003 to 6,215 cases in 2010. Gender ratio of men to women was 1.26. Significant increasing trends of colorectal cancer were observed during the period of the study. The incidence rate increased from 6.22 per 100,000 persons in 2003 to 9.99 in 2010 in males (p<0.001), and it increased from 6.74 per 100,000 persons in 2003 to 8.69 in 2010 in females (p<0.001). Conclusion: Colorectal cancer has an increasing trend in Iran. The rising trend of colorectal cancer as well as other types of cancers is partially due to improvement in cancer registry systems in the early years of registry. Furthermore, westernized lifestyle and an increase in environmental risks could explain this rising trend.